Optimalisasi Peran Pengadilan dalam Penegakan Hukum Pidana di Indonesia - Romualdo Siregar, Boni Halomoan; Debora, Debora (Lembaga Dongan Dosen, 2025)
The court is a core institution in the criminal justice system that is tasked with enforcing the law and providing justice to the community. However, various obstacles such as the slow legal process, the integrity of the apparatus, and limited accessibility are still obstacles. This research aims to analyze the challenges faced by courts in criminal law enforcement in Indonesia, as well as offer strategic solutions through reform, digitalization, and institutional capacity building. The approach used is a normative legal method with the support of secondary data from legal literature and case studies. This article provides practical recommendations to improve the efficiency and credibility of the judiciary.